Combining national forest inventories reveals distinct role of climate on tree recruitment in European forests - Louis A. König; Frits Mohren; Mart-Jan Schelhaas; Julen Astigarraga; Emil Cienciala; Roman Flury; Jonas Fridman; Leen Govaere; Aleksi Lehtonen; Adriane E. Muelbert; Thomas A.M. Pugh; Brigitte Rohner; et al. (Ecological Modelling, 2025)

No evidence that coring affects tree growth or mortality in three common European temperate forest tree species - Jeanne Portier; Ross T. Shackleton; Stefan Klesse; Marco Ferretti; Roman Flury; Martina L. Hobi; Jonas Stillhard; Georg von Arx; Brigitte Rohner; Esther Thürig (European Journal of Forest Research, 2024)
Tree cores are a highly valuable scientific resource. Annual growth ring data can, for example, improve our understanding of climate change impacts and effects of environmental pollution, allow for better annual estimations of tree growth patterns and carbon storage, and help quantify dynamics and changes in forest ecosystems. The value of coring trees for research has been weighted against concerns around the potential harm coring might cause to trees. To date, there is indeed limited research accurately quantifying the potential effects of coring on tree growth and only a handful of studies assessing its influence on mortality. Consequently, many European long-term forest inventorying and monitoring programs are concerned that tree coring might bias the repeated tree measurements in permanent plots, which they rely on for assessments of states and changes of forests. In this study, we assessed the effects of tree coring on the growth and mortality of three widespread European tree species approximately 10 years after they were cored. We used repeated tree measurements from permanent research sites in Switzerland and Ukraine. In Switzerland, we assessed 35 cored and 159 uncored Norway spruce ( Picea abies ) trees as well as 147 cored and 332 uncored silver fir ( Abies alba ) trees. In Ukraine, we assessed 348 cored and 6′611 uncored European beech ( Fagus sylvatica ) trees. We found no statistical evidence that coring negatively affected the growth or mortality of the three tree species assessed. Although we cannot rule out subtle effects on tree health and wood quality, our findings do not provide any evidence that coring affects or biases repeated measurements (such as DBH measures and recording of mortality) performed on the investigated tree species. Tree coring could therefore be considered more often for routine incorporation, particularly in long-term forest inventorying and monitoring programs and initiatives.

Networking the forest infrastructure towards near real-time monitoring – A white paper - Roman Zweifel; Christoforos Pappas; Richard L. Peters; Flurin Babst; Daniel Balanzategui; David Basler; Ana Bastos; Mirela Beloiu; Nina Buchmann; Arun K. Bose; Sabine Braun; Alexander Damm; et al. (Science of The Total Environment, 2023)

Assessing the response of forest productivity to climate extremes in Switzerland using model–data fusion - Volodymyr Trotsiuk; Florian Hartig; Maxime Cailleret; Flurin Babst; David I. Forrester; Andri Baltensweiler; Nina Buchmann; Harald Bugmann; Arthur Gessler; Mana Gharun; Francesco Minunno; Andreas Rigling; et al. (Global Change Biology, 2020)
The response of forest productivity to climate extremes strongly depends on ambient environmental and site conditions. To better understand these relationships at a regional scale, we used nearly 800 observation years from 271 permanent long‐term forest monitoring plots across Switzerland, obtained between 1980 and 2017. We assimilated these data into the 3‐PG forest ecosystem model using Bayesian inference, reducing the bias of model predictions from 14% to 5% for forest stem carbon stocks and from 45% to 9% for stem carbon stock changes. We then estimated the productivity of forests dominated by Picea abies and Fagus sylvatica for the period of 1960–2018, and tested for productivity shifts in response to climate along elevational gradient and in extreme years. Simulated net primary productivity (NPP) decreased with elevation (2.86 ± 0.006 Mg C ha −1 year −1 km −1 for P. abies and 0.93 ± 0.010 Mg C ha −1 year −1 km −1 for F. sylvatica ). During warm–dry extremes, simulated NPP for both species increased at higher and decreased at lower elevations, with reductions in NPP of more than 25% for up to 21% of the potential species distribution range in Switzerland. Reduced plant water availability had a stronger effect on NPP than temperature during warm‐dry extremes. Importantly, cold–dry extremes had negative impacts on regional forest NPP comparable to warm–dry extremes. Overall, our calibrated model suggests that the response of forest productivity to climate extremes is more complex than simple shift toward higher elevation. Such robust estimates of NPP are key for increasing our understanding of forests ecosystems carbon dynamics under climate extremes.

Contrasting resistance and resilience to extreme drought and late spring frost in five major European tree species - Yann Vitasse; Alessandra Bottero; Maxime Cailleret; Christof Bigler; Patrick Fonti; Arthur Gessler; Mathieu Lévesque; Brigitte Rohner; Pascale Weber; Andreas Rigling; Thomas Wohlgemuth (Global Change Biology, 2019)
Extreme climate events (ECEs) such as severe droughts, heat waves, and late spring frosts are rare but exert a paramount role in shaping tree species distributions. The frequency of such ECEs is expected to increase with climate warming, threatening the sustainability of temperate forests. Here, we analyzed 2,844 tree‐ring width series of five dominant European tree species from 104 Swiss sites ranging from 400 to 2,200 m a.s.l. for the period 1930–2016. We found that (a) the broadleaved oak and beech are sensitive to late frosts that strongly reduce current year growth; however, tree growth is highly resilient and fully recovers within 2 years; (b) radial growth of the conifers larch and spruce is strongly and enduringly reduced by spring droughts—these species are the least resistant and resilient to droughts; (c) oak, silver fir, and to a lower extent beech, show higher resistance and resilience to spring droughts and seem therefore better adapted to the future climate. Our results allow a robust comparison of the tree growth responses to drought and spring frost across large climatic gradients and provide striking evidence that the growth of some of the most abundant and economically important European tree species will be increasingly limited by climate warming. These results could serve for supporting species selection to maintain the sustainability of forest ecosystem services under the expected increase in ECEs.

Predicting individual-tree growth of central European tree species as a function of site, stand, management, nutrient, and climate effects - Brigitte Rohner; Peter Waldner; Heike Lischke; Marco Ferretti; Esther Thürig (European Journal of Forest Research, 2018)

A synthesis of radial growth patterns preceding tree mortality - Maxime Cailleret; Steven Jansen; Elisabeth M. R. Robert; Lucía Desoto; Tuomas Aakala; Joseph A. Antos; Barbara Beikircher; Christof Bigler; Harald Bugmann; Marco Caccianiga; Vojtěch Čada; Jesus J. Camarero; et al. (Global Change Biology, 2017)
Tree mortality is a key factor influencing forest functions and dynamics, but our understanding of the mechanisms leading to mortality and the associated changes in tree growth rates are still limited. We compiled a new pan‐continental tree‐ring width database from sites where both dead and living trees were sampled (2970 dead and 4224 living trees from 190 sites, including 36 species), and compared early and recent growth rates between trees that died and those that survived a given mortality event. We observed a decrease in radial growth before death in ca. 84% of the mortality events. The extent and duration of these reductions were highly variable (1–100 years in 96% of events) due to the complex interactions among study species and the source(s) of mortality. Strong and long‐lasting declines were found for gymnosperms, shade‐ and drought‐tolerant species, and trees that died from competition. Angiosperms and trees that died due to biotic attacks (especially bark‐beetles) typically showed relatively small and short‐term growth reductions. Our analysis did not highlight any universal trade‐off between early growth and tree longevity within a species, although this result may also reflect high variability in sampling design among sites. The intersite and interspecific variability in growth patterns before mortality provides valuable information on the nature of the mortality process, which is consistent with our understanding of the physiological mechanisms leading to mortality. Abrupt changes in growth immediately before death can be associated with generalized hydraulic failure and/or bark‐beetle attack, while long‐term decrease in growth may be associated with a gradual decline in hydraulic performance coupled with depletion in carbon reserves. Our results imply that growth‐based mortality algorithms may be a powerful tool for predicting gymnosperm mortality induced by chronic stress, but not necessarily so for angiosperms and in case of intense drought or bark‐beetle outbreaks.

Estimating the age–diameter relationship of oak species in Switzerland using nonlinear mixed-effects models - Brigitte Rohner; Harald Bugmann; Christof Bigler (European Journal of Forest Research, 2013)